Successful Repair of Ruptured Abdominal Aortic Aneurysm: A Case Report - Sharma, Jyotindra (Nepalese Heart Journal, 2003)
Abdominal aortic aneurysms (AAA) are the commonest arterial aneurysms being located mostly in the infrarenal aorta (1). Though pathogenesis of AAA is multifactorial including genetic predisposition, aging, atherosclerosis, inflammation and localised proteolytic enzyme activation, atherosclerotic degeneration of the arterial wall is the most common cause for this. Though other complications like thromboembolism may occur, AAA gains its importance mostly because of the fear of rupture. Aneurysm rupture is the cause of death in 1.2% of males and 0.6% of females in the United States. It is the 13t" most common cause of death in United States killing about 15,000 people annually. Once ruptured the condition carries a high degree of mortality even in the busy centers.